Complete spontaneous resolution of a large post-pneumonic pneumatocele in a 4-year-old child: A case report - Mulham Jarjanazi; Walaa Abbas; Leen Jarjanazi; Bayan Zitani; Mohamed Morjan (Elsevier, 2024)
Introduction: Pulmonary pneumatoceles are thin-walled, air-filled cysts within the lung parenchyma that may present in large sizes and occupy the entire lung field. The may or may not cause symptoms. Case presentation: We report a case of a 4-year-old who presented with fever and cough. Chest X-rays and CT scans revealed a very large airspace in the right lung field measuring 7 × 13 cm, containing several thin septations in its lower area, and surrounded by a thin wall. The right upper lobe was entirely collapsed, while the right lower lobe was partially collapsed. The characteristic radiologic findings supported by the clinical picture led to the diagnosis of a post-pneumonic pneumatocele. Antibiotics were initiated. The patient had no respiratory distress. Serial chest X-rays were done to evaluate the progression of the pneumatocele. The clinical signs and symptoms improved, and we observed a gradual regression of the pneumatocele until it completely disappeared six weeks after his initial hospital admission. Conclusion: Large post-pneumonic pneumatoceles, even those that occupy the majority of a lung field, can remain asymptomatic and be managed conservatively.